Response of Biomass Development, Essential Oil, and Composition of Plectranthus amboinicus (Lour.) Spreng. to Irrigation Frequency and Harvest Time. Issue 3 (9th March 2018) - Sabra, Ali S.; Astatkie, Tessema; Alataway, Abed; Mahmoud, Abeer A.; Gendy, Ahmed S. H.; Said‐Al Ahl, Hussein A. H.; Tkachenko, Kirill G.
Abstract : A greenhouse experiment was conducted to study the effects of four irrigation intervals (4, 8, 12, and 16 days) and six harvests (2, 4, 6, 8, 10, and 12 months after transplanting) on biomass, essential oil content, and composition of Plectranthus amboinicus (Lour .)Spreng . Fresh weight and essential oil yield decreased with increasing irrigation interval; whereas, essential oil content was stimulated by water stress and increased as the irrigation interval increased. Fresh weight of Plectranthus amboinicus irrigated every 4 days peaked when harvested at 6 months, but essential oil content peaked when irrigated every 16 days and harvested at 2 months after transplantation. On the other hand, essential oil yield peaked when irrigated every 8 days and harvested at 6 months. Thymol, p ‐cymene, γ ‐terpinene, and β ‐caryophyllene were the major compounds, and they peaked at different irrigation intervals and harvest times. This study showed biomass, essential oil content, and yield as well as the major and minor constituents of Plectranthus amboinicus are influenced by irrigation interval and the timing of harvest. Abstract :